EDUKASI MANAJEMEN BISNIS GUNA MENGOPTIMALKAN PENGELOLAAN BUMDES DI KECAMATAN BRANG ENE KABUPATEN SUMBAWA BARAT - Suarman, Suarman; Mulawarman, Logi (JUAN: Jurnal Pengabdian Nusantara, 2024)
This activity was carried out by the Brang Ene District Government, West Sumbawa Regency and in collaboration with Bumigora University Lecturers. The activity was conducted on August 27 2023 and involved BUMDes representatives from all villages in Brang Ene District. The stages of implementing this activity consist of 4 implementation steps, namely: Provide information, Reinforce with exercises, Review information, Verify knowledge. Previously, the Team identified that BUMDes management in Brang Ene District was not managing resources and achieving business goals effectively. After implementing education regarding business management, it was found that there was an increase in people's understanding and skills in terms of business management. This activity still requires ongoing support from local governments, educational institutions and other related parties to ensure the success and sustainability of this educational program in optimizing BUMDes management in the region.